A review on selected herbal plants as alternative anti-diabetes drugs: chemical compositions, mechanisms of action, and clinical study - Ahda, Mustofa; Jaswir, Irwandi; Khatib, Alfi; Ahmed, Qamar Uddin; Mahfudh, Nurkhasanah; Ardini, Yunita Dewi (Taylor and Francis, 2023)
Herbal utilization, as an antidiabetes agent, is an interesting topic to find acceptable herbal drugs to decrease blood glucose levels. The aim of this review is to evaluate the potency of selected herbal medicines to reduce blood glucose levels and to identify the chemical compounds responsible for reducing glucose. The mechanisms of action of different herbal medicines used might be also different. The reduction of blood glucose levels by Aloe vera, Andrographis paniculata, and Trigonella foenum-graecum through mini-mum 3 mechanisms of action, such as increased GLP-1 secretion and inhib-ited amylase, glucosidase, and SGLT 2. While Andrographis paniculata has more than 4 mechanisms of action, such as increasing GLP secretion, activat-ing PPAR ɣ-receptor, and also inhibiting amylase, glucosidase, and SGLT 2 but it did not inhibit DPP 4 in diabetic patients.